Health Education in Prevention of Non-Communicable Diseases among Elderly - Fitri, Siti Yuyun Rahayu; Rifa’atul Fitri, Siti Ulfah; Nurhamsyah, Donny (Universitas Padjadjaran, 2025)
Pangandaran is an expansion area of Ciamis Regency, officially established based on Law Number 21 of 2012. Various efforts have been and are being made to achieve progress in line with the mission, vision, and objectives of Pangandaran Regency. Community service, which can serve as a foundation for sustainable regional development, can be directed towards efforts to improve the quality of life of the community from an early stage. The quality of life in elderly is an indicator of the lifestyle a person has led throughout their life. Existing health conditions show that the elderly are vulnerable to non-communicable diseases, with limited access to healthcare services. This community service aims to provide education to the elderly about the prevention of non-communicable diseases and conduct health screenings, including blood pressure, blood sugar, uric acid, and cholesterol tests. The method used was a situational analysis and interactive lectures for the elderly. The activity evaluation uses pretest and posttest analysis. The results show that in the situational study phase, the community was unaware of the prevention and management of non-communicable diseases. After the education, there was an improvement in understanding, reflected by an increase in scores of 0.98, with an average pretest score of 7.34 ± 0.99 and a posttest score of 8.32 ± 0.97. This founding stated there is differences between knowledge before and after education.Keywords: Elderly, healt education, non-communicable diseases.